How to cultivate a sustainable club music ecosystem : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Creative Enterprise, Toi Rauwhārang, Massey University, Wellington, Aotearoa New Zealand - Williamson, Frederick Blyth (Massey University, 2023)
Club music has always been an art-form rooted in community, resistance and freedom. It is a powerful and potent music form that has captured audiences and become a staple in contemporary night life around the world, offering life-affirming moments and a convivial experience of the cities it occupies. This thesis discusses the decline of club music and night life in Wellington, Aotearoa New Zealand and proposes a framework for an authentic experience that creates the foundation of a sustainable club music ecosystem. The research draws on the historical significance of club music as a space for liberation and freedom and highlights the need for such spaces in our current social context, just as they were in 1980s America. Drawing on empirical evidence, this research argues the importance of club spaces in fostering a sense of community to combat isolation in a post covid society. The document draws upon academic literature on club music history, authenticity, scenes and sustainability to support its arguments. The proposed club, T.A.Z., aims to create a transformative and timeless space that delivers an authentic club music experience. The methodology used in the research presents six components that contribute to an authentic club music experience and explores how these can be replicated and sustained, providing the basis for a successful nightclub operation. The exegesis is accompanied by creative works and a business plan which discusses the economic and cultural viability of the proposed club music venue. The research concludes that the proposed ecosystem requires a social institution to develop around suggests that T.A.Z., through delivering an authentic experience, becomes that institution at the nexus of a sustainable club music ecosystem.
Keywords: 360399 Music not elsewhere classified; 470204 Cultural and creative industries